Changes of Testicular Histogenesis during Prenatal and Early Postnatal Life in Bisphenol A Exposed Rats by Ascorbic Acid - Tooba Khurshid, Faiza Umbreen, Tayyaba Faisal, Ayesha Yasser, Tayyaba Qureshi, Amber Rashid (Journal of Rawalpindi Medical College, 2022)
Objectives: In this study we aimed to investigate the conservation of testicular histogenesis in bisphenol A exposed rats by ascorbic acid during prenatal and early postnatal life. Material and Methods: Eight weeks old 15 pregnant rats were divided into 3 groups, each containing 5 rats. Pups were delivered by spontaneous vaginal delivery. Group A had 15 male rat pups, from 5 pregnant female rats, which were fed on standard diet during pregnancy and lactation till day 21. Group B had 15 male rat pups from 5 pregnant female rats which were given 250μg/kg/day Bisphenol A subcutaneously during pregnancy and lactation till day 21. Group C had 15 male rat pups from 5 pregnant female rats which were given 250μg/kg/day Bisphenol A subcutaneously and 150mg/kg/day ascorbic acid orally during pregnancy and lactation till day 21. Results: There was significant deterioration of seminiferous tubule and basement membrane regularity with BPA along with detachment of germinal epithelium and cell debris in group B. These parameters were conserved significantly with ascorbic acid in group C. Conclusion: Biphenol A adversely affects histogenesis of testes by causing oxidative stress when given during pregnancy and lactation and ascorbic acid conserves BPA exposed developing testes and may preserve spermatogenesis and male fertility. Key words: Bisphenol A, ascorbic acid, histogenesis, rat, developing testes, prenatal, early postnatal.